Medical Transgressions in America’s Prisons: Defending Transgender Prisoners’ Access to Transition-Related Care - Agbemenu, Esi (Columbia Journal of Gender and Law, 2015)
With Chelsea Manning’s case making headlines, and hit television show Orange Is the New Black highlighting the struggles of a trans woman in prison, the public is slowly becoming aware of the complex issues facing transgender prisoners. Although it is difficult to determine the precise number of this population, a 2009 study by Brown and McDuffie estimates that approximately 750 prisoners in the United States identify as transgender. This is a relatively small portion of the U.S. prison population, but it represents a sizable portion of America’s transgender population. Nearly one in six transgender Americans—and almost half of the African American transgender population—has been incarcerated in a state or federal prison. Although the issues and concerns of this population have gained more attention in legal scholarship, academia, public policy, and social discourse in recent years, many issues are still largely unresolved for transgender inmates, including their access to medical care. Part I of this Note will provide a background on gender dysphoria and will introduce the concept of prison as a uniquely and problematically gendered space. Part II will introduce the standard of “serious medical need” that is used in Eighth Amendment jurisprudence, with particular focus on how courts have applied this standard to mental health concerns, a category within which gender dysphoria falls. Part III will introduce the central argument that, while increasingly more courts have found gender dysphoria or gender identity disorder to be a serious medical need, they have done so predominantly—and thus problematically—in cases in which the plaintiff has taken extreme measures to remedy his or her lack of treatment. This arguably establishes a pattern whereby attempted suicide and self-surgery become metrics for evaluating the severity of gender dysphoria, and implies that gender dysphoria is not deserving of treatment until it has reached these catastrophic levels. Part IV will address the tension between using medical rhetoric to secure necessary rights for prisoners and avoiding the pathologization of the transgender community that is inherent in the Eighth Amendment argument. Part V will conclude by providing alternative legal arguments as well as broader policy suggestions that may be used alongside the traditional Eighth Amendment argument to secure medical care for transgender inmates.